The medical and socioeconomic factors contributing to the incidence of births by caesarean section in the Philippines - Aganinta, David S. (School of Economics, University of the Philippines Diliman, 2019)
The undergraduate paper will test which medical and socioeconomic factors can cause the incidence of Cesarean births based on Philippine data from a population of women who have experienced delivery by c_section. Using information gathered from the women_s childbearing experience, the thesis paper will aim to discern which of those recalled circumstances may substantially contribute to women having to go through c_section births. The tests aim to estimate impact of the factors in question on the likelihood that the aforementioned event will occur. The study will use the 2013 National Demographic Health Survey as data. Results run from the heckprobit model used show that delivery complications (sepsis and loss of consciousness during delivery), insurance, wealth status, number of alive children, the offspring in the womb being twins, and the mother_s age on birth are factors that contribute the incidence of caesarean births.